Ultrasound Analysis of Respiration-Related Muscles in Rats - Zhan, Shubei; Zheng, Bin; Li, Mengyi; Xu, Lin; Chen, Chengchun; Huang, Peizhen (Frontiers in Genetics, 2022)
The purpose of this study was to evaluate the effectiveness of ultrasound techniques in the analysis of respiratory-related muscles in rats. Respiratory parameters, including diaphragm end-expiratory thickness, mean rectus abdominis (RA) thickness, and RA area, were measured by ultrasound and compared with histological findings. Spearman’s correlation and Logistic regression analysis were used to detect the differences in the correlation between ultrasound results and histological examinations, and Student’s t test was used to compare the differences between ultrasound results and histological examination data. The results showed that there was no significant difference between the end-expiratory thickness of the diaphragm, the average thickness of RA, and the area of RA in the right RA and histological values under ultrasound detection (p > 0.05), but there was a significant positive correlation between ultrasound, and histological values (p < 0.05).); in addition, tidal volume was significantly positively correlated with total RA area, rapid shallow breathing index (RSBI) was significantly negatively correlated with total RA area, and mean diaphragm TF was significantly positively correlated with tidal volume. In conclusion, ultrasound imaging has a high degree of accuracy and reproducibility and can be used to assess the structure and function of the rat diaphragm and RA.